Role of rock structure in drainage development in the Rangit river basin, Sikkim-Darjeeling Himalaya - Nasipuri, Bikram; Jha, Vibhash (National Geographical Journal of India, 2021)
The geology and tectonics of an area play a very important role in the development of geomorphic features and drainage of a region. The Rangit River Basin is a part of Sikkim-Darjeeling Himalaya that contains very significant geological and tectonic characteristics. The basin has mainly three rock groups that are Central Crystalline Complex, the Daling group and the Gondwana group. The spectacular feature of this basin is Rangit Window, where the underlying Gondwana rock group is exposed from overlaying Daling group. Rangit basin exhibits both folded and fault structures which are indeed unique. A detailed study of litho-tectonic setup as well as to identify geomorphic features of this basin geological maps from of Geological Survey of India and topographical maps from Survey of India along with tectonic maps and secondary data have been used. This study is an attempt to show the relation between litho-tectonic setup and drainage development. The river basin is the product of morphotectonics and morphoclimatic mechanisms. Evidence of the faulting, folding, thrusting, fractures and cracks as a witnessed on-field point to the influence of neo-tectonism episodes have been noticed in the study area. Some micro landform features have also been identified after extensive fieldwork in the study area. The present study is an attempt to understand the significant role of rock structure in drainage development in the study area.